CLINICAL COMPARISON OF TYMPANIC MEMBRANE PERFORATION CLOSURE WITH TRICHLOROACETIC ACID AND APAMARGA KSHARA (ACHYRANTHES ASPERA LINN. ALKALINE EXTRACT) - Bhardwaj, *Atul; Agarwal, Riju; Tanwar, Manoj; Kumar, Anoop (International Journal of Ayurveda and Pharma Research, 2016)
Tympanic membrane perforations are broadly pathological and traumatic in origin. The fibrosed rim of perforation and medially migrated epithelial layer of the perforated membrane offers a cauterization opportunity which conspicuously breaks the epithelial barrier, dissolves necrosed tissue over growth and enhances neo membrane formation. Trichloroacetic acid chemical cautery and patching is used from decades in order to reconstitute the tympanic membrane integrity with a successful rate hovering around 85-92% in various clinical studies. Nowhere in the classical Ayurveda texts or in the modern literature Apamarga Kshara (Achyranthes aspera Linn. alkaline extract) paste cauterization is used for re-epithelialization of the tympanic membrane although its tissue generative properties and antimicrobial traits are quite well documented. 34 tympanic membrane perforation patients after ramifying them into two groups were selected for the present clinical study which intends to compare the effectiveness of tympanic membrane perforation closure by application of trichloroacetic acid vis-a-vis application of Achyranthes aspera alkaline extract on the margins of the perforation. Achyranthes aspera alkaline extract for the current clinical trial as a trial drug has its proven tissue regeneration and vasoproliferative properties which is an indispensible prerequisite in any attempt to restore the integrity of a perforated tympanic membrane, also its antimicrobial and vasoproliferative capacity also compliments the selection of Achyranthes aspera alkaline extract. This cauterization with Apamarga Kshara was found to be quite effective as the results were encouraging and can successfully be advocated as an Ayurvedic cauterization substitute for the resurfacing of the ruptured tympanic membrane.